Effects of match situational variables on possession: The case of England Premier League season 2015/16 - Rodrigo Aquino; João P. V. Manechini; Bruno L. S. Bedo; Enrico F. Puggina; Júlio Garganta (Universidade Estadual Paulista (UNESP), 2017)
ABSTRACT Aim The main aim of this study was to identify the effects of match location, quality of opponents and match status on possession during the 2015/16 Season of England Premier League. Methods Three hundred and eighty matches played by 20 teams were analysed. For each match, two values were recorded, resulting in 760 observations. Results Teams who played at home (51.77 ± 10.22%) presented higher possession values (EF=moderate) than those who played away (48.21 ± 10.30%). Quality of opponents also had a significant difference, as possession was higher (EF=large) when teams played against weak (52.30 ± 9.77%) than strong opponents (46.48 ± 10.38%). The multivariate analysis revealed no interaction between situational variables and possession (p = 0.76). Despite the teams classified as "best-ranking" (1st to 8th position: 50.60 ± 10.35%) presented greater possession (EF=moderate) than "worst-ranking" (9st to 20th position: 47.59 ± 9.74%), no significant differences were found in the comparisons of match status (winner [50.34 ± 10.48%] x drawer [49.95 ± 10.25%] x loser [49.68 ± 10.48%]). Conclusion General interpretations should be viewed with caution, since this possession can represent an indicator of success for a team but not for others.